Molecular Identification of Checkered Snapper (Lutjanidae) from Fakfak and Kaimana Waters, Papua - Antajala Rian Maulana; Dewa Gede Raka Wiadnya; Wahyu Endra Kusuma; Destia Fitri Ariyani; Muhammad Dailami; Abdul Hamid A. Toha (Universitas Diponegoro, 2026)
Accurate and rapid species identification of snappers (Lutjanus spp.) is essential for biodiversity assessment and fisheries resource management, particularly in regions with high biodiversity such as the waters of Kaimana and Fakfak, West Papua. This study aimed to identify the economically important checkered snapper (Lutjanus decussatus) using a molecular approach based on DNA barcoding of the cytochrome c oxidase subunit I (COI) gene marker. Six fish tissue samples were collected from the waters of Kaimana and Fakfak, followed by molecular analyses including DNA extraction, PCR amplification, and sequencing. The obtained sequences had a length of 644 base pairs. Sequence data were analyzed by comparison with reference databases using BLAST and the Barcode of Life Data System (BOLD). The results showed that all sample sequences exhibited 100% similarity to reference sequences of L. decussatus in the databases and clustered into a single clade consistently supported by high bootstrap values and low intraspecific genetic distances. The Interspecific and outgroup sequence was clearly separated from the main clade, indicating distinct interspecific divergence. These findings demonstrate the effectiveness of COI-based DNA barcoding for species identification of L. decussatus, and the obtained genetic information can support further studies on genetic diversity and resource management in West Papua.